Sympathectomy induces novel purinergic sensitivity in sciatic afferents - Chen Yong; Zhang Yi-Hong; Bie Bi-Hua; Zhao Zhi-Qi (Acta Pharmacologica Sinica; Vol 21, No 11 (November 2000): Acta Pharmacologica Sinica, 2016)
"AIM: To test the hypothesis that sympathectomy could induce novel purinergic sensitivity in sciatic afferents. METHODS: Teased-fiber recordings were made from 32 spontaneously active A afferents from the sciatic nerves in surgically sympathectomized rats and 30 spontaneously active A afferents from the sciatic nerves in intact rats. Adenosine 5'-triphosphate (ATP) was injected via a cannula in jugular vein. RESULTS: Twenty eight percent of the spontaneously active afferent fibers from sciatic nerves in the sympathectomized rats responded to ATP, either with an increase or with a decrease in spontaneous firing. However, none of the fibers from the sciatic nerves in the intact rats was activated by ATP. CONCLUSION: Sympathectomy induces novel purinergic sensitivity in A afferents from sciatic nerve."